Diplomatic ceremonial events at the 1821 Congress of Ljubljana - Udovič, Boštjan (Studia Historica Slovenica, 2023)
The article focuses on ceremonial events at the often-neglected 1821 Congress of Ljubljana, on related media reports, and on the impact of these events on how the Congress proceeded. The analysis brings two main findings. Firstly, ceremonial events during the Congress of Ljubljana of 1821 were an important part of the Congress, and were also covered extensively by the media. Secondly, the aim of the Austrian political elite in organising the ceremonial events that accompanied the Congress of Ljubljana was not only to grease the wheels of diplomatic talks, but also to pursue a policy of its prestige, including by setting the esprit de corps of the main political leaders of the era.
Keywords: ceremonial; Diplomacija; diplomatski protokol; Ljubljana; Ljubljana Congress; Ljubljanski kongres; Ljubljanski kongres 1821; music; prestige; Sveta aliansa; theatre; Zgodovina